If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(4b + -2) = 2(8b + 1) Reorder the terms: 9(-2 + 4b) = 2(8b + 1) (-2 * 9 + 4b * 9) = 2(8b + 1) (-18 + 36b) = 2(8b + 1) Reorder the terms: -18 + 36b = 2(1 + 8b) -18 + 36b = (1 * 2 + 8b * 2) -18 + 36b = (2 + 16b) Solving -18 + 36b = 2 + 16b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-16b' to each side of the equation. -18 + 36b + -16b = 2 + 16b + -16b Combine like terms: 36b + -16b = 20b -18 + 20b = 2 + 16b + -16b Combine like terms: 16b + -16b = 0 -18 + 20b = 2 + 0 -18 + 20b = 2 Add '18' to each side of the equation. -18 + 18 + 20b = 2 + 18 Combine like terms: -18 + 18 = 0 0 + 20b = 2 + 18 20b = 2 + 18 Combine like terms: 2 + 18 = 20 20b = 20 Divide each side by '20'. b = 1 Simplifying b = 1
| 2/3x+9=7/6 | | x^2+6x-3=x+a^2+b | | 20/12+12y-8=60 | | 4t+11=6t-15 | | 9-7x=9x+23 | | 2C+8=7C-42 | | -7=3(9-5)-9 | | -42-7x=9x+23 | | 5n+5(1-n)=n+8 | | -1k=-6 | | 6X+4=-4+7X | | 4y+12(y+10)=92 | | 45x+22.7=15 | | 3*4-3*8= | | 16x+6=96-4x | | F+4/g | | 3r+7r=-r-4r | | -6y-7=5y-9 | | q+14=8(9+7) | | -4+M=2M-16 | | (3x+10)(5x-10)=180 | | 10(5+3x)-11(9+8x)=515 | | 3(2x+9)-4x+11=-20 | | (3x-10)(5x-10)=180 | | q+4=8(q+7) | | 2g+4=21 | | 5x+5=-5+3x+20 | | X+9=-13+3X | | -x+3=x-1 | | 5x+112=14x-14 | | 3.2+x=3.2 | | 3(1/4m-1/2)+3/4m=3/2 |